Industrial training report: Medical Record Department, An-Nur Hasanah Specialist Hospital / Nurul Fazilah Suhaimi - Suhaimi, Nurul Fazilah (Bachelor of Information Science (Hons.) Records Management, 2015)
This report presents the industrial training activities I have been trained at the Medical Records Unit, An-Nur Hasanah Specialist Hospital (HPAN) within 5 months. The training activities assigned are regarding to the records management field. During the industrial training, I have carried out a special project about transferring medical records to the new record storage space. As a result, from this project I have generated a guideline for transferring medical records to the new record storage space which includes the several steps in transferring process of records. Besides that, the project is run smoothly and successfully carried out within the period given. There are a lot of lesson learned from workplace can be as an experience before entering the real job world. So, in order to gain more knowledge, there is should be a self-exploration for obtaining that additional knowledge.